From the Pineal Gland to the Central Clock in the Brain: Beginning of Studies of the Mammalian Biological Rhythms in the Institute of Physiology of the Czech Academy of Sciences - Illnerová, H (Physiological research, 2024)
The Institute of Physiology of the Czech Academy of Sciences (CAS) has been involved in the field of chronobiology, i.e., in research on temporal regulation of physiological processes, since 1970. The review describes the first 35 years of the research mostly on the effect of light and daylength, i.e., photoperiod, on entrainment or resetting of the pineal rhythm in melatonin production and of intrinsic rhythms in the central biological clock. This clock controls pineal and other circadian rhythms and is located in the suprachiasmatic nuclei (SCN) of the hypothalamus. During the early chronobiological research, many original findings have been reported, e.g. on mechanisms of resetting of the pineal rhythm in melatonin production by short light pulses or by long exposures of animals to light at night, on modulation of the nocturnal melatonin production by the photoperiod or on the presence of high affinity melatonin binding sites in the SCN. The first evidence was given that the photoperiod modulates functional properties of the SCN and hence the SCN not only controls the daily programme of the organism but it may serve also as a calendar measuring the time of a year. During all the years, the chronobiological community has started to talk about "the Czech school of chronobiology". At present, the today´s Laboratory of Biological Rhythms of the Institute of Physiology CAS continues in the chronobiological research and the studies have been extended to the entire circadian timekeeping system in mammals with focus on its ontogenesis, entrainment mechanisms and circadian regulation of physiological functions. Key words: Pineal, Melatonin, AA-NAT rhythm, Light entrainment, Photoperiod, SCN clock.
Keywords: mozek; cirkadiánní rytmus; Humans; History, 21st Century; melatonin; Academies and Institutes; fotoperioda; dějiny 20. století; History, 20th Century; lidé; dějiny 21. století; zvířata; akademie a ústavy; Circadian Rhythm; Circadian Clocks; nucleus suprachiasmaticus; Brain; epifýza mozková; Photoperiod; cirkadiánní hodiny; biologické hodiny; Animals; Pineal Gland; Biological Clocks; Suprachiasmatic Nucleus; Melatonin